Measuring Financial Reporting and the Extent of Compliance with its Standards by Private Sector Units - Sahib, Abdulrasool Abdulabbas (Technium Business and Management, 2025)
This research aims to identify the mechanisms and areas of application of international financial reporting standards and to what extent financial reporting affects the investment decision-making process that will drive growth forward through the activation of the financial markets; the most important conclusion reached by the researchers is that most of the companies listed in the Iraqi Stock Exchange did not adequately report their financial statements, but instead did not provide the necessary clarifications about the procedures or changes in their financial statements, the researchers recommend that the Securities and Exchange Commission should take the measures needed to compel companies to abide by international financial reporting standards by requesting the amendment of some laws or regulations or taking some deterrent measures that help improve the media content of financial statements.